Blood Flow Restriction Accelerates Recruitment During a High-Intensity Non-Volitional Task - Richardson, Lyric; Olmos, Alex; Montgomery, Tony; Burleson, Kylie; Succi, Pasquale; Lubiak, Sean M; Dinyer-McNeely, Taylor K; Hammer, Shane M; Bergstrom, Haley C; Hill, Ethan C; Trevino, Michael A (International Journal of Sports Medicine, 2025)
This study examined blood flow restriction (BFR) usage and motor unit (MU) behavior of the biceps brachii during a single high-intensity contraction. Twelve resistance-trained males (25±5 y) completed maximal voluntary contractions (MVCs) of the elbow flexors, followed by a 70% MVC with BFR and without BFR (CON). Surface electromyographic (EMG) signals from the 70% MVCs were decomposed to extract MU: recruitment thresholds (RTs), action potential amplitudes (MUAPAMPS), and mean firing rates (MFRs). EMG amplitude (EMGRMS) at 70% MVC was normalized (N-EMGRMS) to MVC EMGRMS. Paired samples t-tests compared the y-intercepts and slopes of the MUAPAMP and MFR vs. RT relationships and N-EMGRMS between treatments. For the MUAPAMP vs. RT relationships, the y-intercepts were greater (p=0.016) for CON than BFR, whereas the slopes were greater (p=0.024) for BFR than CON. For the MFR vs. RT relationships, the y-intercepts were greater (p=0.039) for BFR than CON, whereas the slopes were more negative (p=0.023) for BFR than CON. N-EMGRMS was greater (p=0.038) for BFR than CON. BFR accelerated higher-threshold MU recruitment, increased lower-threshold MU firing rates, and increased N-EMGRMS during a single high-intensity muscle action. BFR may be beneficial for accelerating MU recruitment in populations/scenarios where near-maximal efforts are contraindicated.
Keywords: biceps brachii; elbow flexors; electromyography